2023
DOI: 10.1016/j.jvoice.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Objective Speech Assessment of Smoking Status based on Voice Features: A Review of the Literature

Abstract: Background and Objective: In smoking cessation clinical research and practice, objective validation of self-reported smoking status is crucial for ensuring the reliability of the primary outcome, that is, smoking abstinence. Speech signals convey important information about a speaker, such as age, gender, body size, emotional state, and health state. We investigated (1) if smoking could measurably alter voice features, (2) if smoking cessation could lead to changes in voice, and therefore (3) if the voice-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Smoking has been shown to impact voice measures such as voice pitch or stability (e.g. see Ma et al, 2020). In a previous study from our group, we showed that smoking voices are perceived more negatively than non-smoking voices by naive listeners (Lortie, Deschamps, Guitton, & Tremblay, 2018).…”
Section: Personal and Environmental Factors Related To Voice Disordersmentioning
confidence: 48%
“…Smoking has been shown to impact voice measures such as voice pitch or stability (e.g. see Ma et al, 2020). In a previous study from our group, we showed that smoking voices are perceived more negatively than non-smoking voices by naive listeners (Lortie, Deschamps, Guitton, & Tremblay, 2018).…”
Section: Personal and Environmental Factors Related To Voice Disordersmentioning
confidence: 48%
“…92% of the teachers who participated in the study said smoking harms their voice. Fundamental frequency, jitter, shimmer, harmonics-to-noise ratio, and other voice features are affected by smoking [14] .…”
Section: Resultsmentioning
confidence: 99%
“…As per the result analysis, The participants showed a significant decrease in the F0 range, which indicates a reduction in the ability to modulate pitch; intonation patterns were altered; speech rate increased significantly after alcohol consumption, with longer pauses between sentences; and a decrease in the ability to accentuate syllables. Ma et al (2021) [13] presented a comprehensive existing literature review on voice features for the smoking estimation objective. The review provides an overview of the various voice characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%